2013
DOI: 10.1159/000346335
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Immunotherapy for Experimental Allergic Conjunctivitis in a Murine Model Induced by Dermatophagoides farinae Allergen

Abstract: Background: Sublingual immunotherapy (SLIT) is a clinically effective treatment in allergic conjunctivitis (AC); however, the mechanism of the underlying pharmacodynamics remains unclear. Here, we investigate the efficacy and the mechanism of a sublingually administered Dermatophagoides farinae (Der f) vaccine in a murine AC model. Methods: A murine model of AC caused by Der f extract was developed in BALB/c mice by repeated application of allergen. Sensitized mice were SLIT treated by Der f drops and subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Desensitization was performed simultaneously with sensitization step from 0 to 8 week in accordance with the following procedure (Table 1), and this procedure was refer to Der f drops' clinical application [14]. The Der f drops (Chanllergen) was provided by Zhejiang Wolwo Bio-Pharmaceutical Co., Ltd. [15].…”
Section: Sublingual Administration Of Desensitizationmentioning
confidence: 99%
“…Desensitization was performed simultaneously with sensitization step from 0 to 8 week in accordance with the following procedure (Table 1), and this procedure was refer to Der f drops' clinical application [14]. The Der f drops (Chanllergen) was provided by Zhejiang Wolwo Bio-Pharmaceutical Co., Ltd. [15].…”
Section: Sublingual Administration Of Desensitizationmentioning
confidence: 99%
“…In a mouse model of ocular allergy using Dermatophagoidesfarinae , sublingual immunotherapy (SLIT) reduced clinical symptoms and the associated Th2 responses (110). Interestingly, SLIT in patients with allergic asthma to the same allergen had reduced symptoms that correlated with reduced Th17 cells and increased Tregs (111).…”
Section: T Helper Cells In Ocular Allergymentioning
confidence: 99%
“…In addition, the presence of a glycogen-rich content in the cytoplasm of epithelial cell detected only in minipigs and monkeys also supports the inference that such cells are similar to those of humans. In line with these observations, several studies conducted in allergy murine models showed that higher doses (fifty to a hundred times more) of allergen are required for a successful treatment in allergic mice when compared to doses administered to humans in the course of AIT [ 31 37 ]. Consequently, such models only approximate the human situation regarding allergen dosage and administration schemes.…”
Section: Discussionmentioning
confidence: 89%